Kajian Tri Hita Karana Ekowisata Berorientasi Kesejahteraan - Sari, AA PT Agung Mirah Purnama; Suindari, Ni Made (Jurnal Ilmiah Pariwisata; Vol 25 No 3 (2020): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v25i3.1353, 2020)
Apart from providing benefits, the existence of tourist objects can also have a negative impact. However, the possible negative impact can be controlled by applying the Tri Hita Karana concept to tourist objects. A combination of quantitative and qualitative research or commonly called mix method is used in this research. This study aims to analyze the effect of tukad bindu ecotourism on community welfare and to determine the application of Tri Hita Karana in tukad bindu. The results showed that the development of tukad bindu ecotourism did not significantly affect the standard of living of the surrounding community. This is because the development of tukad bindu ecotourism has only been running for two years since 2017. The existence and development of the tukad bindu has a positive effect on the community, especially in the economic, environmental and social aspects of the moderate category. Tri Hita Karana in tukad bindu has been implemented quite well in the moderate category. Keywords: Tukad Bindu; Ecotourism; Tri Hita Karana; Welfare